Projectively Vanishing Nearly Cosymplectic Manifold - Abood, Habeeb M.; Mohammed, Nawaf J. (Communications in Mathematics and Applications, 2018)
The present paper focuses on the study of the geometric properties of projective curvature tensor on the nearly cosymplectic manifold. In particular, the flatness properties of projective tensor have been studied, so related to these properties we defined three special classes of nearly cosymplectic manifold.